Pelayanan Kebutuhan Spiritual dalam Menghadapi Perilaku Mal Adaptif Anak di Yayasan Panti Asuhan Amal Wanita - Rafif Pratama; Moh Amin (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Adaptive mall behavior, can be said as behavior that is not according to demands environment maladaptive behavior as behavior that is not desired that could be disruptive individual adaptive function in his daily life. This research aims to know about spiritual services to address behavior adaptive mall children become adaptive. This research uses qualitative approach with descriptive methods. Informant determination techniques with purpusive sampling, data collection techniques using interviews, observation and documentation Meanwhile, analysis techniques data using triangulation. The research results show that form of behavior children's adaptive mall in Women's Charitable Orphanage Foundation includes: likes playing truant, fighting and smoking. As for service needs spiritual includes reciting the Koran , prayer, and studying religious knowledge.